Ashitaba (Angelica keiskei) leaves extract cream 8% inhibited the increase of melanin amount as effective as hydroquinone cream 4% and inhibited the increase of tyrosinase enzymes not as effective as hydroquinone cream 4% in the ultraviolet B-exposed Guin - Chynthia Friama; Anak Agung Gde Putra Wiraguna; Wimpie Pangkahila (Neurologico Spinale Medico Chirurgico, 2021)
Background: Excessive sun exposure results in increased activity of the tyrosinase enzyme and the amount of melanin in the skin which causes hyperpigmentation, a sign of premature aging. The purpose of this study was to prove that Ashitaba (Angelica keiskei) leaves extract cream 8% inhibited the increase of melanin and tyrosinase enzymes as effective as hydroquinone cream 4% in the ultraviolet B-exposed guinea pig (Cavia porcellus) skin. Methods: This study used a randomized post-test only control group design. The subjects were 36 male guinea pigs (Cavia porcellus). Subjects were divided into two groups, the hydroquinone cream 4% group and the Ashitaba leaves extract cream 8% group exposed to UVB light. Skin samples were collected 48 hours after the last exposure to measure the tyrosinase enzyme levels using the ELISA method and the amount of melanin was examined by Masson-Fontana staining. Results: The mean levels of tyrosinase in the hydroquinone cream 4% group was 19.51 ± 5.16 ng/L and the Ashitaba leaves extract cream 8% group was 23.76 ± 3.09 ng/L (p = 0.005). The mean amount of melanin in the hydroquinone cream 4% group was 2.98 ± 2.27% and the Ashitaba leaves extract cream 8% group was 4.77 ± 3.33% (p = 0.069). Conclusion: The administration of Ashitaba (Angelica keiskei) leaves extract cream 8% inhibited the increase of melanin amount as effective as hydroquinone cream 4% and inhibited the increase of tyrosinase enzymes not as effective as hydroquinone cream 4% in the ultraviolet B-exposed guinea pig (Cavia porcellus) skin.